Breaking the spell : religion as a natural phenomenon - Dennett, D. C. (Daniel Clement) (New York : Viking, 2006)
An innovative thinker tackles the controversial question of why we believe in God and how religion shapes our lives and our future. For a growing number of people, there is nothing more important than religion. It is an integral part of their marriage, child rearing, and community. In this daring new book, distinguished philosopher Dennett takes a hard look at this phenomenon and asks why. Where does our devotion to God come from and what purpose does it serve? Is religion a blind evolutionary compulsion or a rational choice? In a narrative that ranges widely through history, philosophy, and psychology, Dennett explores how organized religion evolved from folk beliefs and why it is such a potent force today. He contends that the "belief in belief" has fogged any attempt to rationally consider the existence of God and the relationship between divinity and human need.--From publisher description
Breaking which spell? -- Some questions about science -- Why good things happen -- The roots of religion -- Religion, the early days -- The evolution of stewardship -- The invention of team spirit -- Belief in belief -- Toward a buyer's guide to religions -- Morality and religion -- Now what do we do? -- Appendixes: The new replicators ; Some more questions about science ; The bellboy and the lady named Tuck ; Kim Philby as a real case of indeterminacy of radical interpretation
Includes bibliographical references (pages 413-426) and index
Keywords: Anthropology of religion; Psychology, Religious; Religion -- History; Religion -- Controversial literature; Controversial literature